Mechanism for the transition to digitalization of forestry enterprises using correlation analysis - Shanin Igor; Shtondin Anatoly (BIO Web of Conferences)
This paper presents the results of a scientific study based on the conducted economic and mathematical modelling. The author's model of key conditions for the use of information and communication technologies (ICT) in the structure of innovative digital optimization of business processes is proposed. Based on the presented model, an integral indicator for assessing the level of provision of innovative development in the context of the transition to import-substituting products, taking into account the crisis and sanctions, is formed. Taking into account the developed integral indicator, the optimality coefficients of the indicators of the group of forestry enterprises were developed, determining the degree of use of digital resources (Kdrfc) and the optimality of the indicators of financing the digitalization of forestry enterprises (Kfdfc). A correlation analysis of the digitalization data of forestry enterprises was carried out. According to the calculation results, it was revealed that the highest level of correlation is noted for variables (y2i) and (y2.3i), caused by the introduction of the latest production equipment based on the use of modern digital technologies. The largest increase is observed in the pulp and paper industry, with a level of 219112.18, according to the results of 2023, but in comparison with the same base period (2020), a significant increase is observed, where the value of the variable (y2.3i) was 148286.57. The most successful, according to the coefficient of optimality of indicators of the use of digital resources of the group of forestry enterprises in digitalization (Kdrfc), are enterprises engaged in furniture production with a variable (x1.4ij) with an index of 0.235, with (Iael) = 7.412.